Inhalation technique practical skills and knowledge among physicians and nurses in two pediatric emergency settings. (1st February 2021) - Spaggiari, Stéphanie; Gehri, Mario; Di Benedetto, Laurence; Hafen, Gaudenz M.; Pauchard, Jean-Yves; Gervaix, Alain; Pannatier, André; Sadeghipour, Farshid; Di Paolo, Ermindo R.
Abstract: Introduction: Correct technique with a pressurized metered-dose inhaler (pMDI) equipped with a valved holding chamber (VHC) or spacer provides an important advantage for adequate control of asthma and virus-induced wheezing in young children. The aim of this study was to assess the ability and knowledge of physicians and nurses to use a pMDI with a masked VHC in two pediatric emergency units. Methods: Study design: Two-center observational study. Inhaler use technique was assessed in 50 physicians and 50 nurses using a child mannequin and a validated videotaped nine-step scoring method. The participants' knowledge was evaluated by a questionnaire. Results: The inhalation technique was perfectly mastered by 49% of the study participants and almost perfectly mastered by another 34% (mean score 8.3 ± 0.7; range 5–9). Nurses were more likely than doctors to demonstrate the technique perfectly (66% vs. 32%, p < 0.05). The two most common errors were forgetting to shake the pMDI between two consecutive puffs (38% of the participants) and putting the patient in an incorrect position (11%). About half of the participants reported that they checked each patient's inhalation technique at every opportunity and knew how to clean the VHC. A large majority did not employ a reliable method to determine the amount of medication remaining in pMDIs without a counter. Conclusion: Healthcare professionals' practical skills and knowledge on inhalation therapy were not completely mastered and could be improved with a mandatory training program.